Identification of SIRT3 modulating compounds in deep-sea fungi metabolites: Insights from molecular docking and MD simulations - Abdullah R. Alanzi; Bayan Abdullah Alhaidhal; Raghad Mohammad Aloatibi (PLoS ONE, 2025)
SIRT3, a crucial deacetylase that plays a key role in regulating mitochondrial acetylation, is tightly linked to metabolic processes and is essential for the maintenance of eukaryotic life. SIRT3 is a potential therapeutic target due to its key role in various diseases, including ageing, heart disease, cancer, and metabolic disorders. In this work, we aimed to identify potential SIRT3 inhibitors from the deep-sea fungal metabolites by employing molecular docking and ADMET analysis. Based on the binding affinities, ten compounds were selected whose docking scores were in the range of -9.693 to -8.327 kcal/mol. Further, four compounds Penipanoid C, Penicillactam, Quinolonimide, and Brevianamide R were selected based on the ADMET properties and subjected to Molecular dynamics simulations to assess the stability of these molecules with target. The stability analysis indicated that the selected compounds could act as lead compounds during in vitro assays to advance these drug candidates towards clinical drug development.